Prognostic impact of angiotensin-converting enzyme inhibitors and receptor blockers on recurrent ventricular tachyarrhythmias and implantable cardioverter-defibrillator therapies - Schupp, Tobias; Behnes, Michael; Weiß, Christel; Lang, Siegfried; Akın, Ibrahim; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Borggrefe, Martin (Journal of cardiovascular pharmacology, 2019)
Abstract: This study sought to assess the prognostic impact of treatment with angiotensin-converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB) on recurrences of ventricular tachyarrhythmias in recipients of implantable cardioverter-defibrillators (ICD). Using a large retrospective registry including consecutive ICD recipients with documented episodes of ventricular tachycardia (VT) or fibrillation (VF) from 2002 to 2016, those patients treated with ACEi/ARB were compared with patients without. The primary prognostic endpoint was the first recurrence of ventricular tachyarrhythmias and related ICD therapies at 5 years. Multivariable Cox regression analyses were applied within the entire cohort, and thereafter, Kaplan-Meier analyses were performed in propensity-matched subgroups. A total of 592 consecutive ICD recipients were included (81% treated with ACEi/ARB and 19% without). Although ACEi/ARB was associated with no differences in overall recurrence of ventricular tachyarrhythmias, ACEi/ARB was associated with improved freedom from appropriate ICD therapy within multivariable Cox regressions (hazard ratio = 0.666; P = 0.043), especially in patients with index episodes of VF, left ventricular ejection fraction <35%, coronary artery disease, secondary preventive ICD, and glomerular filtration rate <45 mL/min/1.73 m2. In the propensity-matched subgroup, ACEi/ARB still prolonged freedom from appropriate ICD therapies (hazard ratio = 0.380; 95% confidence interval 0.193-0.747; P = 0.005). In conclusion, ACEi/ARB therapy was associated with improved freedom from appropriate ICD therapies.
Gesehen am 24.02.2020